Total synthesis and biological evaluation of cell adhesion inhibitors peribysin A and B: structural revision of peribysin B - Kalmode, Hanuman P.; Handore, Kishor L.; Rajput, Raveena; Shaikh, Samir R.; Gonnade, Rajesh G.; Kulkarni, Kiran A.; Reddy, D. Srinivasa (Organic letters, 2018)
Total synthesis of potent cell-adhesion inhibitors peribysins A and B has been accomplished for the first time in racemic form. A Diels-Alder/aldol sequence to build the skeleton and decoration of the desired functionalities of the targeted natural products using highly stereoselective operations are the highlights. The structures of synthesized peribysins were fully characterized using spectral data and single-crystal X-ray analysis. Through this total synthesis, the initially proposed structure of peribysin B has been revised. Furthermore, the cell-adhesion inhibition potential of the scaffold (two peribysins + three analogues) was confirmed using anti-adhesion assay.

Overturning the peribysin family natural products isolated from periconia byssoides OUPS-N133: synthesis and stereochemical revision of peribysins A, B, C, F, and G - Athawale, Paresh R.; Kalmode, Hanuman P.; Motiwala, Zenia; Kulkarni, Kiran A.; Reddy, D. Srinivasa (Organic Letters, 2020)
Herein we report the stereochemical revision of peribysins A, B, C, F, and G, guided by enantiospecific total synthesis starting from (+)-nootkatone. Furthermore, we reconfirmed the absolute stereochemistry of peribysin Q The highlights of the synthesis are enone transposition and kinetic iodination resulting in separation of diastereomers. Our findings coupled with synthetic and biological data previously reported by Danishefsky's group suggest that the original stereochemistries of peribysins A, B, C, F, and G were misassigned.

Postmodification of voxelotor (GBT 440) via [Rh]-catalyzed cross dehydrogenative coupling with olefins br - Kalshetti, Rupali G.; Rajput, Raveena; Motiwala, Zenia; Reddy, D. Srinivasa; Kulkarni, Kiran A.; V. Ramana, Chepuri (Bioorganic & Medicinal Chemistry Letters, 2022)
The directed Rh(III)-catalyzed cross dehydrogenative coupling of the pyrazole unit of the GBT-440 scaffold has been explored with simple as well as conjugated olefins to synthesize post-functionalized GBT-440 analogues. The screening of these synthesized compounds for improving the oxygen binding efficiency of the hemoglobin isolated from the sickled red blood cells revealed that some of these compounds are as good as GBT-440.
Keywords: CDC Coupling; GBT-440 (Voxelotor); Rh(III) catalysis; sickle cell anemia

Synthesis, biological evaluation and docking studies of silicon incorporated diarylpyrroles as MmpL3 inhibitors: an effective strategy towards development of potent anti-tubercular agents - Vasudevan, N.; Motiwala, Zenia; Ramesh, Remya; Wagh, Sachin B.; Shingare, Rahul D.; Katte, Revansiddha; Anand, Amitesh; Choudhary, Sushil; Kumar, Ajay; Gokhale, Rajesh S.; Kulkarni, Kiran A.; Reddy, D. Srinivasa (European Journal of Medicinal Chemistry, 2023)
Growing global demand for new molecules to treat tuberculosis has created an urgent need to develop novel strategies to combat the menace. BM212 related compounds were found to be potent anti-TB agents and they inhibit mycolic acid transporter, MmpL3, a known potent drug target from Mycobacterium tuberculosis. In order to enhance their inhibitory potency, several silicon analogues of diarylpyrroles related to BM212 were designed, synthesized, and evaluated for anti-tubercular activities. In Alamar blue assay, most of the silicon-incorporated compounds were found to be more potent than the parent compound (BM212), against Mycobacterium tuberculosis (MIC = 1.7 & mu;M, H37Rv). Docking results from the crystal structure of MmpL3 and silicon analogues as pharmacophore model also strongly correlate with the biological assays and suggest that the incorporation of silicon in the inhibitor scaffold could enhance their potency by stabilizing the hydrophobic residues at the binding pocket. The best docking hit, compound 12 showed an MIC of 0.1 & mu;M against H37Rv with an acceptable in vitro ADME profile and excellent selectivity index. Overall, the present study indicates that, the designed silicon analogues, especially compound 12 could be a good inhibitor for an intrinsically flexible drug-binding pocket of MmpL3 and has potential for further development as anti-tubercular agents.
Keywords: antibiotic; BM212; docking studies; MmpL3 inhibitor; Silicon analogue; tuberculosis